Extraction Techniques, Biological Activities and Health Benefits of Marine Algae Enteromorpha prolifera Polysaccharide - Wassie, Teketay; Niu, Kaimin; Xie, Chunyan; Wang, Haihua; Xin, Wu (Frontiers in Nutrition, 2021)
There is increasing interest in the use of marine algae as functional food additives for improving human health. Enteromorpha (Ulva) prolifera (E. prolifera) is a seaweed green alga (Chlorophyta) that contains many bioactive compounds, of which polysaccharide is the main component. With the advancement of technology in the methods of extraction and analysis, recent studies in in vitro and animals model showed that polysaccharides derived from E. prolifera exert various biological activities, such as gut microbiota modulation, immunomodulation, antioxidant, antidiabetic, antimicrobial, and hypolipidemic. Research evidence has shown that methods of extraction and molecular modification, such as degradation, carboxymethylation, and sulfonation could alter the biological activities of polysaccharides. Therefore, in this review, we discussed the different extraction techniques, structural-activity relationship, and health benefits of sulfated polysaccharides derived from E. prolifera, and suggested future research avenues. This review helps to advance the extraction techniques and promote the application of marine algae polysaccharides as functional food and therapeutic agent.